The Effect of Work Stress and Workload on The Performance Of Nurses In The Inpatient Installation Of Muhammadiyah Babat Lamongan Hospital - Ahmad Ghulam Amrullah Rahim (International Conference on Economics, Management, Business, and Accounting, 2025)
This study aims to analyze the effect of work stress and workload on the performance of nurses in the Inpatient Unit of Muhammadiyah Babat Hospital. The research employs a quantitative method with a descriptive and associative approach. The sample consists of 36 nurses selected through a saturated sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability, and then analyzed using the Statistical Package for the Social Sciences (SPSS) with multiple linear regression analysis. The results indicate that partially, work stress and workload have no significant effect on nurse performance, whereas simultaneously, both variables have a significant effect on performance. The coefficient of determination (R²) of 33.4% shows that work stress and workload together explain the variability in nurse performance, while the remaining 66.6% is influenced by other factors outside the model. These findings suggest that there are other dominant factors influencing nurse performance. The results of this study are expected to serve as an empirical reference for academics in developing studies related to human resource management in the health sector, as well as a practical consideration for hospital management in designing strategies to improve the performance of nursing personnel in a more holistic and measurable manner.